Analisis Unsur Fisik dan Batin pada Puisi Hatiku Selembar Daun, Dalam Doaku, Gerimis Jatuh, kita Saksikan Karya Sapardi Djoko Damono (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
The poems in Sapardi Djoko Darmono's work have beauty and meaning that need to be analyzed. This research aims to analyze the physical and mental elements in four poems, namely Hatiku Selembar Daun by Sapardi Djoko Damono, In My Prayers, Gerimis Falling in Love, and Kita Saksi-saksi. The method used is qualitative descriptive with a structural approach, which focuses on the study of the internal structure of poetry, including physical elements such as diction, imagery, rhyme, and language style, as well as mental elements such as themes, tone, feelings, and mandates. The results of the analysis show that the four poems have a distinctive power of expression in conveying the poet's inner experience. The physical element is used effectively to reinforce the atmosphere and meaning, while the inner element reflects the struggle of emotions, spirituality, and deep reflection on life and love. The entire poem shows the typical characteristics of modern Indonesian poetry which is full of meaning and aesthetics.